Reconnecting River-City: A Visibility and Accessibility Assessment of the Ping River’s View Characters in Chiang Mai City - Janjira Sukwai; Nattasit Srinurak (Heritage)
A river’s landmarks have advantages in attracting people to engage with natural/historical settings. However, uncontrolled development can have negative effects on the visual and obstruct people’s access. In this context, researchers have highlighted obstacles to these landmarks and suggested features of the relationship between the visibility and accessibility to these landmarks, aiming to preserve heritage sites. This project evaluated riverscape landmarks to develop a strategic urban design that uses scientific and spatial toolkits to maintain the historic landmark on the riverside in Chiang Mai city. The methodology utilized for GIS included visibility and accessibility assessments as variables for analyzing interconnections and classification utilizing the statistical method of hierarchical clustering analysis (HCA). The findings indicate differences in the accessibility of angular step coverage (ASC) and walking distance coverage (WDC), which have an impact on landmark designation. The city-level landmarks have the highest ASC, while various religious landmarks display the highest visibility. These factors have a unique impact on the HCA results, which are categorized into six groups that are consistent with the historical content and purpose of the landmarks. The clustered groups represent the strategic design of the riverscape, which necessitates policies to enhance the potential for preserving these icons as part of the historic landscape.